THE ANALYSIS OF FORMS AND MEANINGS OF PREFIXES FOUND IN BALI ADVERTISER - Dewa Ayu Kadek Claria (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
The title of this research is The Analysis Forms and Meanings of Prefixes Found in Bali Advertiser. The scopes of discussions in this research are the forms of prefixes found in Bali Advertiser and their meanings. The method in doing this research is qualitative research. The data source which is used in writing this research is Bali Advertiser, a newspaper which is used for advertisement for foreign community, and it is also used as the official English language media for the Direktorat Jenderal Pajak (Bali Tax Office). The main theory which is used in this research is the theory of Quirk in the book entitled A University Grammar of English. The books which are used as supporting theory are Morphology by Katamba and English Word - Formation by Bauer. After collecting and analyzing the data, there are many forms and meanings of prefixes found, they are: negative prefixes such as non-,and in-, reversative or privative prefixes such as un- and dis-, pejorative prefixes that is mis-, prefixes of degree or size such as super-, out-, sur-, over-, ultra- and mini-, prefixes of attitude such as co- and anti-, locative prefixes that is inter-, prefixes of time and order such as pre-, ex-, and re-, number prefixes such as bi- and multi-, other prefixes such as auto- and semi-, and conversion prefixes such as be- and en-.